2007
DOI: 10.1097/01.ijg.0000243476.43837.d6
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculectomy With Mitomycin C in Secondary Glaucoma Associated With Behçet Disease

Abstract: Trabeculectomy with MMC provides reduction of IOP and the number of antiglaucoma medications in cases with secondary glaucoma associated with BD in a 1-year follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Yalvac et al 12 achieved overall 1-, 2-, 3-, 4-, and 5-year success rates of 83%, 76%, 70%, 66%, and 62%, respectively, in 26 eyes treated with trabeculectomy and MMC. Almost same success rate with BD, 82%, was achieved for the first year of trabeculectomy and MMC by Elgin et al 14 Similar results have been reported for nonselective uveitic 16 with success rates of 70% at 34 months and 50% at 5 years, respectively. Late failure rates are higher than those reported for trabeculectomy in patients with nonuveitic glaucoma.…”
Section: Discussionsupporting
confidence: 84%
“…Yalvac et al 12 achieved overall 1-, 2-, 3-, 4-, and 5-year success rates of 83%, 76%, 70%, 66%, and 62%, respectively, in 26 eyes treated with trabeculectomy and MMC. Almost same success rate with BD, 82%, was achieved for the first year of trabeculectomy and MMC by Elgin et al 14 Similar results have been reported for nonselective uveitic 16 with success rates of 70% at 34 months and 50% at 5 years, respectively. Late failure rates are higher than those reported for trabeculectomy in patients with nonuveitic glaucoma.…”
Section: Discussionsupporting
confidence: 84%
“…5,6 Despite this it remains a common first line surgical procedure in these cases, particularly when augmented with Mitomycin C (MMC) or 5-Fluorouracil (5-FU). [6][7][8][9][10][11][12] This may reflect the widespread choice of trabeculectomy as the preferred primary procedure by many glaucoma surgeons, which still leaves the option of subsequent glaucoma drainage implantation (GDI) if necessary. There are increasing numbers of reports in the literature regarding the use and efficacy of GDI for UG with some authors suggesting this as a primary procedure in all cases with a high failure risk.…”
Section: Introductionmentioning
confidence: 99%
“…The surgical procedure of choice is probably trabeculectomy with mitomycin C (MMC) as evidenced by a number of recent reports (6)(7)(8)(9)(10)(11). This is perhaps because it is the preferred procedure for primary glaucoma for most ophthalmic surgeons.…”
Section: Introductionmentioning
confidence: 99%